Strategi Pembelajaran Baca Tulis Al-Qur’an dalam Menguatkan Aqidah dan Akhlak: Analisis Muatan Lokal di Kota Bogor - Najamudin; Dede Dang Sudjana; Dwi Muliati; Ahmad Reza (Institut Muslim Cendekia, 2026)
Amid the disruption of the digital era and the threat of moral degradation, Qur’an Reading and Writing (BTA) learning faces significant challenges. Currently, BTA often gets caught up merely in cognitive and psychomotor aspects, such as reading fluency, while neglecting the affective aspect or the internalization of spiritual values into the students' souls. This study aims to analyze BTA learning strategies as a local content subject in their function to strengthen students' faith and character foundations, going beyond mere technical reading skills. This study uses a qualitative method with a library research approach. Data were collected through a literature analysis related to local content policies, Qur’an teaching methods, and character formation theory. The results of the study indicate that effective BTA learning strategies must integrate three main pillars: a competency-based curriculum and regional potential that emphasizes manners. Methods The reception and habituation that connect the verses of the Qur'an with the values of monotheism in a practical way. A holistic approach that positions the Qur'an as a fortress against extreme thinking and radicalism. This study offers a reorientation of Qur'an Reading and Writing learning from merely eradicating Qur'anic illiteracy to becoming a strategic instrument for strengthening ideology (aqidah) and morality (akhlaq) through a local content curriculum that is adaptive to the challenges of the times. Policymakers at the regional level are advised to develop a BTA curriculum guide that not only focuses on administrative reading graduation targets but also includes character achievement indicators (akhlaq) as a primary requirement for graduate competencies.